2021
DOI: 10.35799/jis.v21i2.35684
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity Testing on APMS (p-Methoxy Cinnamic Acid) Against Escherichia coli Bacteria

Abstract: This study aims to determine whether the compound APMS (p-methoxy cinnamic acid) has the antibacterial activity of Escherichia coli and to determine the effective concentration of the compound APMS (p-methoxy cinnamic acid) in inhibiting the growth of Escherichia coli bacteria. This research begins with the synthesis of APMS obtained through the knoevenagel condensation reaction with the sonochemical method. The synthesized compounds were tested organoleptically and their melting points were measured. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In addition, sonochemical are easy to operate and minimize waste. This Previous studies on cinnamic acid have shown that this compound can be used as a photoprotective agent [10], and PMCA has the potential as an antibacterial against E. coli [3]. In addition, cinnamic acid derivatives also showed activity as a sunscreen [11][12][13].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, sonochemical are easy to operate and minimize waste. This Previous studies on cinnamic acid have shown that this compound can be used as a photoprotective agent [10], and PMCA has the potential as an antibacterial against E. coli [3]. In addition, cinnamic acid derivatives also showed activity as a sunscreen [11][12][13].…”
Section: Introductionmentioning
confidence: 91%
“…P-methoxy cinnamic acid is one of the cinnamic acid derivative compounds substituted for a methoxy group at the para position [1]. The compound p-methoxy cinnamic acid has activity as an antibacterial [2][3], an anti-inflammatory and anticancer [4], antioxidant, antidiabetic [5], hepatoprotective, neuroprotective, and chemopreventive activity [1]. P-methoxy cinnamic acid can be obtained through a hydrolysis reaction by transforming ethyl p-methoxycinnamate from the isolation of natural ingredients, namely aromatic ginger (Kaempheria galanga L.) [2] and the Perkin reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Asam pmetoksisinamat merupakan senyawa hasil reaksi 2 tahap etil p-metoksisinamat yang diketahui memiliki aktivitas antibakteri. [9], antiinflamasi [10], antidiabetes, neuroprotektif, aktivitas kemopreventif, antioksidan, dan hepatoprotektif [11].…”
Section: A Pendahuluanunclassified